La “Barra” en los congresos de Colombia y Chile, siglo XIX - Galán-Guerrero, Luis Gabriel; Posada-Carbó, Eduardo (Jahrbuch für Geschichte Lateinamerikas, 2019)
This article examines the role that ‘barras’ (public galleries) played in Congress in nineteenth-century Colombia, including comparative references to other Latin American countries, especially to Chile. After some introductory remarks, different aspects of the ‘barras’ are analysed. The first section offers a general characterization of the level of attendance to the galleries and of the people attending them, by focusing on its popular background. The second section explores the ‘barras’ political practices and motives driving their actions. By doing so, it tries to establish its possible impact on parliamentary business. The evidence provided allows us to offer some concluding remarks and to put forward the following argument: the ‘barras’ were a fundamental component of the political culture that developed in a few Latin American countries following their independence from Spain.